Humanism Counseling: Finding Gaps in the Concept of Religious Guidance and Counseling in Indonesian Government Regulation (Normative Study of Government Regulation No. 111/2014) - Indri Indri; Usman Abu Bakar; Abdul Matin bin Salman (Syntax Corporation Indonesia, 2021)
This paper finds and explains the side of the discussion of religion in government regulation no. 111/2014. The results show that there is no vacancy in the discussion of religion in this regulation. One of the functions of guidance and counseling services is understanding, which is to help counselees have a better understanding of themselves and their environment (education, work, culture, and religious norms). In its application, guidance and counseling services in educational units as a whole are packaged into four service components, one of which is the basic service component, where the main objective is an effort to help counselees have awareness (understanding) of themselves and their environment (education, work, social culture, and religion). While the concept of communication guidance and counseling services that religion is a fixed(intended)and services that are not fixed (unintended), which subsequently gave birth to concepts counseling humanism.